2018
DOI: 10.21470/1678-9741-2018-0084
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury after Cardiac Surgery in Patients Without Chronic Kidney Disease

Abstract: IntroductionAmong patients undergoing cardiac surgery, the occurrence of acute renal injury appears to be associated with worse prognosis and increased mortality. The objective of this study was to evaluate risk factors and the impact this complication on mortality and survival after cardiac surgery among patients without chronic kidney disease.MethodsIn this retrospective study, we reviewed the medical records of 142 patients who underwent elective coronary artery bypass grafting, valve replacement (single or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 28 publications
4
27
1
2
Order By: Relevance
“…In the present study, 31% of the included patients developed AKI. Other studies showed an incidence of AKI to range from 43.6% [20] to 47% [21] in post cardiac surgery patients. These differences between other studies and ours may be related to differences in study design, patients' profile, and diagnostic criteria.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, 31% of the included patients developed AKI. Other studies showed an incidence of AKI to range from 43.6% [20] to 47% [21] in post cardiac surgery patients. These differences between other studies and ours may be related to differences in study design, patients' profile, and diagnostic criteria.…”
Section: Discussionmentioning
confidence: 95%
“…Based on the random-effects model, the highest prevalence of acute renal failure in patients undergoing cardiac surgery in Brazil was 45.7% (47.6% 43.6-47.8%, CI = 95%) [22,24,27] [25,32,35,40]. Finally, the prevalence of acute renal failure in Italy was 10.6% (9.8-11.3%, CI = 95%) [28,31,39] (Fig.…”
Section: The Meta-analysis Of the Prevalence Of Acute Renal Failure Amentioning
confidence: 97%
“…A total of 21 studies from 6 countries that met the inclusion criteria were reviewed. Among these studies, 7 studies were from United States (25,34,(36)(37)(38)41,42), 4 studies from Canada (25,32,35,40), 3 studies from Brazil (22,24,27) 3 studies from Italy (28,31,39), one study from England (30), one from Uruguay (23), and one was study from New England (29). Convenient sampling was used to select the participants (n = 21).…”
Section: Research Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations